(untitled) (Chichester, 2016)
This book covers recent developments in process systems engineering (PSE) for efficient resource use in biomass conversion systems. It provides an overview of process development in biomass conversion systems with focus on biorefineries involving the production and coproduction of fuels, heating, cooling, and chemicals. The scope includes grassroots and retrofitting applications. In order to reach high levels of processing efficiency, it also covers techniques and applications of natural-resource (mass and energy) conservation. Technical, economic, environmental, and social aspects of biorefineries are discussed and reconciled. The assessment scales vary from unit- to process- and life-cycle or supply chain levels. The chapters are written by leading experts from around the world, and present an integrated set of contributions. Providing a comprehensive, multi-dimensional analysis of various aspects of bioenergy systems, the book is suitable for both academic researchers and energy professionals in industry.
Keywords: Hóa chất sinh học,Biomass chemicals